2013
DOI: 10.1038/pr.2013.73
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of dehydroepiandrosterone on pulmonary hypertension in a rodent model of pulmonary hypertension in infants

Abstract: Background: Pulmonary hypertension (PH) is a disease that affects the adult or infant population. Dehydroepiandrosterone (DHEA), a steroid hormone, has been previously shown to prevent and to reverse PH in an adult rat model. We thus investigated its effect in a rat-pup model of chronic hypoxic PH. Methods: Animals were maintained for 3 wk in a hypobaric chamber to induce PH, with or without concomitant treatment with DHEA (30 mg/kg every alternate day). results: DHEA significantly reduced mean pulmonary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The animal model protocol of PH infant rats was carried out in accordance with a previous study . Fifteen days after birth, female Wistar rats with their neonatal pups were divided into five groups evenly and randomly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal model protocol of PH infant rats was carried out in accordance with a previous study . Fifteen days after birth, female Wistar rats with their neonatal pups were divided into five groups evenly and randomly.…”
Section: Methodsmentioning
confidence: 99%
“…The phenotypes of PH in infants can be divided into four subtypes: (a) congenital heart disease related (infants often with left–right shunt congenital heart diseases; (b) acute or chronic hypoxia related; (c) neonatal developmental defect related; and (d) idiopathic forms . Remodeling of the small pulmonary arteries is the leading manifestation of the pathology of PH , and it was reported that airway inflammation played important roles in this process, contributing to the development of PH . However, the exact mechanism is still not clear.…”
mentioning
confidence: 99%
“…At the cellular level, DHEA reduces hypoxia-induced accumulation of hypoxia-inducible factor 1α (HIF)-1α in human pulmonary artery endothelial cells (hPAECs) [35] and stimulates NO release in bovine endothelial cells (ECs) [36]. In animals, preventive and/or rescue treatments with DHEA or DHEA-S are effective in CH-PH [37][38][39], MCT-PH [40,41], fetal pulmonary circulation in sheep [42], the rat model of PH in infants [43], and in Sugen 5416 + hypoxia (Su-Hx)-induced PH [44]. DHEA also attenuates PH in patients with chronic obstructive pulmonary disease [45].…”
Section: Sult-sts Pathway In Pahmentioning
confidence: 99%
“…The delicate balance between DHEA and DHEA-S is controlled by the relative activity of sulfotransferase (DHEA → DHEA-S) and sulfatase (DHEA-S → DHEA) [26]. Both DHEA and DHEA-S are protective in experimental models of pulmonary hypertension [27][28][29][30][31] including models of angioproliferative PH [32,33]. Recently, lower DHEA-S and higher E2 levels have been linked to a greater risk of PAH and worse hemodynamics, functional status, and greater risk of death [34,35].…”
Section: Increased Estradiol Production In Pahmentioning
confidence: 99%